Socioecological Resilience: contributions and challenges from Anthropology - Escalera Reyes, Javier; Ruiz Ballesteros, Esteban (Revista de Antropología Social, 2011)
The need of a complex understanding of the territories and its evolution is being addressed through notions such as adaptive complex system and socio-ecosystem. Environmental sensitivity is increasingly a socio-environmental sensitivity. So sustainability has begun to be reformulated from the Nature Sciences through the concept of socio-ecological resilience, claiming a transdisciplinarity that is capable of operationally articulate the natural and cultural dimensions of the environment. The participation of Social Anthropology in this process is key insofar it can provide a solid perspective on: (1) the development of notions as socioecosystem and socio-ecological resilience; (2) the debate on the relationship between culture and nature; and (3) the ethnography as an especially appropriate methodology to understand socio-natural reality. The text goes forward in this theoretical and methodological reflection through our recent research in Ecuador and Costa Rica.
Keywords: socio-ecological resilience; socioecosystem; environment; sustainability